Entre páginas e passados sombrios: a presença do holocausto, nazismo e totalitarismo nas histórias em quadrinhos - SOUZA, João Vitor Gomes de (2023)
This work studies the possibilities linked to the use of Comics in History teaching, especially graphic works that present in their content plots that correspond to concepts such as Nazism, Totalitarianism and the Holocaust, in general the period corresponding to the Second World War. , not to mention that the work also proposes to present the characteristics of graphic works, the challenges, the contributions to teaching and historiographical research, to expose that comic books are a rich source for the debate of historiographical themes, the work also seeks to discuss the proposed concepts based on the analysis of authors specialized in the themes, in addition, the work is concerned with presenting excerpts from comic books that have direct links with the chosen concepts, promoting a relationship between academic bibliography and moments of five selected comics, which are Maus, The Search, The Plot, X-Men Magneto and Family Secret and in its conclusion the work proposes to present possibilities to teachers on how they can approach the Holocaust, Nazism and similar themes in the classroom using comic books, promoting more dynamic and useful teaching.